A Linear Parameter Varying Approach for Robust Dead-Time Compensation ⁎. Issue 1 (2019) - Morato, Marcelo Menezes; Normey-Rico, Julio E.
Abstract: This paper proposes a novel method for the design of time-varying dead-time compensators. The presented approach is a modified version of Filtered Smith Predictor (FSP), extended with a delay estimator and a Linear Parameter Varying (LPV) feedback filter. Just as with the FSP, this scheme can be tuned for an adequate trade-off between perfomance and robustness, as well as for unstable and integrative processes. The LPV filter (scheduled by the estimation of the dead-time) is used to overcome the time-varying delay as it autonomously adapts itself and imposes, accordingly, more/less robustness to the closed-loop. Simulation results considering the temperature control of a Solar Collector Field are given to illustrate the method's performance towards reference tracking, disturbance rejection and uncertainty.